Human Umbilical Cord Mesenchymal Stem Cell-Derived Extracellular Vesicles Promote the Proliferation of Schwann Cells by Regulating the PI3K/AKT Signaling Pathway via Transferring miR-21 - Yongbin Ma; Dan Zhou; Huanyan Zhang; Liming Tang; Fen Qian; Jianhua Su (Hindawi Limited, 2021)
As an alternative mesenchymal stem cell- (MSC-) based therapy, MSC-derived extracellular vesicles (EVs) have shown promise in the field of regenerative medicine. We previously found that human umbilical cord mesenchymal stem cell-derived EVs (hUCMSC-EVs) improved functional recovery and nerve regeneration in a rat model of sciatic nerve transection. However, the underlying mechanisms are poorly understood. Here, we demonstrated for the first time that hUCMSC-EVs promoted the proliferation of Schwann cells by activating the PI3K/AKT signaling pathway. Furthermore, we showed that hUCMSC-EVs mediated Schwann cell proliferation via transfer of miR-21. Our findings highlight a novel mechanism of hUCMSC-EVs in treating peripheral nerve injury and suggest that hUCMSC-EVs may be an attractive option for clinical application in the treatment of peripheral nerve injury.